Monitoring Interactions and Dynamics of Endogenous Beta-catenin With Intracellular Nanobodies in Living Cells - Traenkle, Bjoern (Mol Cell Proteomics, 2015)
β-catenin is the key component of the canonical Wnt pathway and plays a crucial role in a multitude of developmental and homeostatic processes. The different tasks of β-catenin are orchestrated by its subcellular localization and participation in multiprotein complexes. To gain a better understanding of β-catenin's role in living cells we have generated a new set of single domain antibodies, referred to as nanobodies, derived from heavy chain antibodies of camelids. We selected nanobodies recognizing the N-terminal, core or C-terminal domain of β-catenin and applied these new high-affinity binders as capture molecules in sandwich immunoassays and co-immunoprecipitations of endogenous β-catenin complexes. In addition, we engineered intracellularly functional anti-β-catenin chromobodies by combining the binding moieties of the nanobodies with fluorescent proteins. For the first time, we were able to visualize the subcellular localization and nuclear translocation of endogenous β-catenin in living cells using these chromobodies. Moreover, the chromobody signal allowed us to trace the accumulation of diffusible, hypo-phosphorylated β-catenin in response to compound treatment in real time using High Content Imaging. The anti-β-catenin nanobodies and chromobodies characterized in this study are versatile tools that enable a novel and unique approach to monitor the dynamics of subcellular β-catenin in biochemical and cell biological assays.